2010
DOI: 10.1074/jbc.m109.064238
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Regulation of Hepatic Nuclear Factor 1α by NKX6.1 in Pancreatic Beta Cells

Abstract: Hepatic nuclear factor 1␣ (HNF1␣) is a key regulator of development and function in pancreatic beta cells and is specifically involved in regulation of glycolysis and glucose-stimulated insulin secretion. Abnormal expression of HNF1␣ leads to development of MODY3 (maturity-onset diabetes of the young 3). We report that NK6 homeodomain 1 (NKX6.1) binds to a cis-regulatory element in the HNF1␣ promoter and is a major regulator of this gene in beta cells. We identified an NKX6.1 recognition sequence in the distal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 57 publications
0
22
0
1
Order By: Relevance
“…Maturity‐onset diabetes of the young (MODY) is a heritable, monogenic form of diabetes . The majority of patients with MODY have mutations in the hepatocyte nuclear factor 1α ( HNF1A ) gene (HNF1A diabetes or MODY3), which result in reduced concentrations of ATP in β cells, and in turn lower insulin secretion . Furthermore, ~20% of white people with HNF1A mutations are obese or overweight, and the HNF1A locus predisposes obese young people to diabetes, implying a link between HNF1A and obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Maturity‐onset diabetes of the young (MODY) is a heritable, monogenic form of diabetes . The majority of patients with MODY have mutations in the hepatocyte nuclear factor 1α ( HNF1A ) gene (HNF1A diabetes or MODY3), which result in reduced concentrations of ATP in β cells, and in turn lower insulin secretion . Furthermore, ~20% of white people with HNF1A mutations are obese or overweight, and the HNF1A locus predisposes obese young people to diabetes, implying a link between HNF1A and obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Sources: For references to linkages that had been established earlier, see caption to predecessor of this GRN (Davidson, 2006, p. 179). More recent sources of data supporting the linkages shown in this GRN model, both positive and negative, are as follows: PTF1 to ptf1a, PTF1 to exocrine genes, PTF1 to RBP-JL (Beres et al, 2006); (ptf1a, RBP-JL) to pdx1 (Miyatsuka et al, 2007;Wiebe et al, 2007); (mafa, mafb) to pdx1 (Vanhoose et al, 2008); (foxa1, foxa2) to pdx1 (Gao et al, 2008); (foxa, nkx2.2, pdx1) to mafa (Raum et al, 2006); glis3 to mafa, glis3 to insulin, glis3 to pdx1, glis3 to ngn3 (Fernandez-Zapico et al, 2009;Kang et al, 2009); (islet1, hnf4a) to insulin, (Eeckhoute et al, 2006;Zhang et al, 2009);(meis, pbx1, pbx2) to pax6 (Zhang et al, 2006;Delporte et al, 2008); nkx6.1 to hnf1α (Donelan et al, 2010); (nkx2.2, ngn3) to neuroD (Anderson et al, 2009); (pdx1, gata4) to gata4 (Rojas et al, 2009);(nkx6.1, pdx1, pax6) to mafa (Raum et al, 2010); foxa to gata4 (Rojas et al, 2010); pax6 to mafb, pax6 to c-maf, pax6 to neuroD1, and (mafb, neuroD1, foxa1, foxa2) to glucagon (Gosmain et al, 2010); islet1 to arx (Liu et al, 2011); dac to cyc21 (Kalousova et al, 2010); hnf1a to mafa ; pdx1 to pax6 (Delporte et al, 2008); ngn3 to ia1 (Mellitzer et al, 2006); hnf4a to hnf1α (Lu et al, 2008); pax6 to glucagon (Grapp et al, 2009); pbx1 to glucagon (Liu et al, 2006); (pax6, cmaf) to glucagon ; nk6.1 to glucagon (Gauthier et al, 2007); brn4 to glucagon, (pdx1, mafa, neuroD) to pander (Burkhardt et al, 2008); alx3 to insulin (Mirasierra and Vallejo, 2006;Mirasierra et al, ...…”
Section: Regulatory Regionalization Of the Mammalian Gutmentioning
confidence: 99%
“…Recently, it was demonstrated that Hnf-1␣ expression is directly activated by Nkx6.1 binding to a newly identified cisregulatory element in the distal region of the Hnf-1␣ promoter (Donelan et al 2010). Nkx6.1 is a homeodomain transcription factor that plays a role in pancreatic development as well as maintenance of ␤ cell function in mature ␤ cells (Lyttle et al 2008).…”
Section: Hnf-1␣ Deficiency Impairs ␤ Cell Growth Proliferation and mentioning
confidence: 99%